Acinetobacter sedimenti sp. nov., isolated from beach sediment. Issue 11 (25th November 2022) - Zheng, Kaiwen; Hong, Yi; Guo, Zhen; Debnath, Sanjit Chandra; Yan, Cen; Li, Kejing; Chen, Gen; Xu, Jinzhong; Wu, Fabai; Zheng, Daoqiong; Wang, Pinmei
Abstract : A Gram-stain-negative, aerobic, non-motile, non-haemolytic, oxidase-negative, catalase-positive bacillus strain (A3.8 T ) was isolated from beach sediment from Zhairuo Island, PR China. The strain grew at pH 6.0–9.0 (optimum, 7.0), with 0–4.5 % NaCl (optimum, 2 %) and at 10–35 °C (optimum, 30 °C). Its whole-genome sequence was 2.5 Mb in size, with a DNA G+C content of 41.6 mol%. On the basis of the results of core genome phylogenetic analysis, A3.8 T represents a separate branch within the clade formed by five species of the genus Acinetobacter with 'Acinetobacter marinus' as the most closely related species. The average nucleotide identity compared with the closely related species of the genus Acinetobacter was below 83.66 % and digital DNA–DNA hybridization values were less than 28.80 %. The predominant fatty acids included C18 : 1 ω9 c, C16 : 0 and summed feature 3 (C16 : 1 ω7 c and/or C16 : 1 ω6 c ). Q-9 was the major respiratory quinone. The polar lipids are mainly composed of diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, two phospholipids, an aminolipid and four unknown lipids. A3.8 T cannot assimilate dl -lactate and weakly utilizes l -glutamate, l -leucine, l -phenylalanine and l -tartrate, which distinguishes it from other species of the genus Acinetobacter . On the basis of the genotype, phenotype and biochemical data, strain A3.8 T represents a novel species of the genus Acinetobacter, for which the name Acinetobacter sedimenti sp. nov. is proposed. The type strain is A3.8 T (=MCCC 1K07161 T =LMG 32568 T ).